(untitled) (Perner’s Contacts, 2009)
The article deals with usage of modern road cargo-transport vehicles in logistic transport chains. Main of them are: double-deck vehicles, semitrailers with extended length and “European Modular System” (EMS) vehicles as well. Main characteristics and their role in logistics are summed up here.